1978
DOI: 10.1073/pnas.75.4.1984
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma pigmentosum neurological abnormalities correlate with colony-forming ability after ultraviolet radiation.

Abstract: Xeroderma pigmentosum is an autosomal recessive disease in which DNA repair processes are defective. All xeroderma piginentosum patients develop premature aging of sun-exposed skin, and some develop neurological abnormalities due to premature death of nerve cells. Sensitivity-to ultraviolet radiation of 24 xeroderma pigmentosum fibroblast strains was studied in vitro by measuring each strain's ability to divide and form colonies after irradiation. The most sensitive strains were derived from patients who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(73 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…3 illustrates what we will refer to as the accumulated DNA damage mechanism for neurodegeneration due to DNA repair deficiency. This mechanism was originally proposed by Robbins and co-workers to explain the neurodegeneration observed in XP patients [24]. According to this mechanism, in normal individuals endogenous DNA damage is constantly being produced but also repaired, resulting in a low-steady-state level of damage which is compatible with normal cellular function.…”
Section: Caveatsmentioning
confidence: 89%
See 1 more Smart Citation
“…3 illustrates what we will refer to as the accumulated DNA damage mechanism for neurodegeneration due to DNA repair deficiency. This mechanism was originally proposed by Robbins and co-workers to explain the neurodegeneration observed in XP patients [24]. According to this mechanism, in normal individuals endogenous DNA damage is constantly being produced but also repaired, resulting in a low-steady-state level of damage which is compatible with normal cellular function.…”
Section: Caveatsmentioning
confidence: 89%
“…However, it is worth noting that at the time the mechanism [24] was originally proposed, it was very controversial and not at all well received (J. Robbins, personal communication) in part because at the time there was much less knowledge of the magnitude of endogenous DNA damage than today.…”
Section: Caveatsmentioning
confidence: 99%
“…Robbins and colleagues (Andrews et al, 1978) compared the relative survival of cells from different XP patients with or without XP neurological disease to different doses of UVradiation. These authors observed a strong correlation between reduced cell survival after UV and the severity of XP neurological disease.…”
Section: Xp Neurological Disease Results From Defective Ner Repairmentioning
confidence: 99%
“…The focus of this manuscript is to discuss the neurological disease in patients with xeroderma pigmentosum (XP), the first example of a neurological disease associated with defective DNA repair (Andrews et al, 1978). I will first review the clinical and neuropathological characteristics of XP neurological disease, as well as the evidence that it results from defective nucleotide excision repair (NER).…”
Section: Introductionmentioning
confidence: 99%
“…Patients in groups XP-A, -D, and -G are considered to be the most severe (12), with early-onset neurological degeneration and abnormally severe sunburn reactions, whereas XP-C is considered to be intermediate, and XP-E and variant are the least severely affected. Although in some respects this is correct, especially in conditions in which UVR protection and early diagnosis is difficult, we found that early diagnosis and rigorous UVR protection can have profound effects on clinical features.…”
Section: Discussionmentioning
confidence: 99%